Development of Phytoremediation Module Based on Research Results - Yulis, Putri Ade Rahma; Nafsi, Radhiatun; Desti, Desti; Suryanti, Suryanti; Sari, Yelfira (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop and examine the validity of module development based on the research outcome on Phytoremediation. This phytoremediation material was one of the topics in the Biotechnology course studied by Biology Education students. The research method used research and development with the ADDIE model, namely analysis, design, development, implementation, and evaluation. However, this research was conducted until the development stage.Â The data were the percentage of product validity from validation sheets and the responses obtained from validation results by material and media experts. Limited trials were subsequently conducted on students of Biology Education who had taken Biotechnology classes. The data analysis technique used qualitative and quantitative descriptive analysis. The validation results based on the material experts were 79.74% (very valid), while based on the learning experts, it was 97.50% (very valid). Then, the results of small group trials obtained a percentage of 90.70% (very valid). moduleModules development was very valid and feasible to be implemented. This module was expected to raise the studentsâ€™ effectiveness in attending lectures because the source of teaching materials was more applicable.